Defense Diplomacy: The role of the French military bases in the African continent - هاني البسوس; فاطمة السويدي (مجلة العلوم السياسية, 2023)
This research seeks to study the role of military bases in activating defense diplomacy, with a focus on studying the case of France in the African continent, which relied on its military bases as a tool to implement its foreign policy. The research explains the concept of defense diplomacy and its relationship to military bases as an effective tool to strengthening bilateral relations between the state's parties. The research focuses on studying the effectiveness of military bases as a tool for activating French defense diplomacy, and studying the goals that French foreign policy seeks to achieve through its intervention or presence in the African continent. In addition to the geopolitical reasons that prompted France to move towards the African continent and plant its military bases. In order to complete this study and achieve its objectives, it adopts the historical approach and the descriptive analytical approach to search documents and studies related to the interpretation of French political behavior in the African continent. The study concludes that France is keen to protect its interests and achieve its external goals by employing various tools, including defensive diplomacy represented in its military bases in the lands of other countries. It also concludes that the nature of the historical stage that France went through and the exploitation of its bases and military presence in implementing its higher interests at the expense of the African people led to the failure of French foreign policy in African countries